Health status, function, productivity, and costs among individuals with idiopathic painful peripheral neuropathy with small fiber involvement in the United States: results from a retrospective chart review and cross-sectional survey. (June 2014) - Schaefer, Caroline; Mann, Rachael; Sadosky, Alesia; Daniel, Shoshana; Parsons, Bruce; Nalamachu, Srinivas; Stacey, Brett R.; Tuchman, Michael; Anschel, Alan; Nieshoff, Edward
Abstract Objective: To characterize the burden of idiopathic painful peripheral neuropathy with small fiber involvement (idiopathic SFN) by pain severity in the US. Methods: One hundred previously diagnosed idiopathic SFN subjects were enrolled during routine office visits. Subjects completed a one-time questionnaire, and investigators reported clinical characteristics and healthcare resource use, based on 6 month retrospective chart review. Annualized direct and indirect costs were estimated. Results were stratified across pain severity groups. Results: Mean age was 63.5 years; 53.0% were female; 76.0% had moderate or severe pain. Most common comorbidities were sleep disturbance/insomnia (37.0%), anxiety (34.0%), and depressive symptoms (33.0%). Overall mean health status (0.59; −0.11–1.00 scale), physical and mental health (31.7 and 45.6, respectively, 0–100 scale), sleep index (45.1; 0–100 scale), and pain interference with function (5.0; 0–10 scale) differed by pain severity, with worse outcomes among those with greater pain (all p < 0.002). 84.0% were prescribed ≥1 SFN medication. 16.0% were employed; mean overall work impairment was 36.9%. Annualized average adjusted direct and indirect costs per subject ($8055 and $13, 733, respectively) differed by pain severity. Conclusions: Idiopathic SFN subjects with pain experience moderate or severe pain, which negatively impacts health status, function, and productivity, and leads to substantial direct and indirect costs.